Discourses, trends, and scenarios for managing the crisis caused in the tourism sector by COVID-19 - Reyes, Mauricio (2022)
The crisis caused by COVID-19 put all the tourist activity on the planet in check and the managers of the sector are faced with a panorama of high degree of uncertainty when making decisions to define the direction of the organizations that they comprise. The following work tries to clarify the complex panorama through a qualitative study of discourses, trends and possible scenarios.